Barrier to entry and feasibility of community based corn seed agribusiness: study case in Sigi Regency Central Sulawesi. Issue 1 (April 2020) - Rahayu, Heni SP; Irmadamayanti, A.; Febrianti, T.; Syafruddin,; Ishak, A.B.L
Abstract: The availability of corn seed at the farm level with reachable price plays an important role in the productivity of corn farming. However the sustainability of this agribusiness mostly depends on how its marketing exists. This paper investigates barriers to entry and feasibility in based community seed corn agribusiness to get sustainable business. The study used a survey to 20 member of based community corn seed breeder and the evaluation of other breeder groups under the supervision of the Field School Seed Independent Program hat have been carried out in the period of 2015 to 2018. The study also has survey in market structure of seed corn in Central Sulawesi especially Sigi District. The data were descriptively analysed. The result shows that corn seed agribusiness was feasible with Benefit Cost Ratio 1, 06 in partnership system. While an assessment identifies some activities with negligible entry barriers, a notable cost of entry is associated with most activities including promotion cost. Other concern barriers are economies of scale, distribution network, high competitive market with incumbent producer based on quality product, differentiation product, and promotion systems. Based on direct superior seed distribution or BLBU procurement policy, market opportunities especially for Research and Development hybrid corn varieties are still promising considering there is 26% gap between corn seed production and demand in Sigi Regency and wider in Central Sulawesi.